1984
DOI: 10.1159/000206386
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Alterations in Blood and Bone Marrow of Ribavirin-Treated Monkeys

Abstract: The antiviral drug ribavirin (1, β-D-ribofuranosyl-1,2,4-triazole-3-carboxamide) produced significant hematologic effects when administered to rhesus monkeys by intramuscular injection over 10 days in doses of 30 or 100 mg/kg/day. The monkeys developed dose-related progressive anemia and thrombocytosis associated with marrow erythroid hypoplasia and megakaryocyte hyperplasia. In addition, bone marrow examination revealed phagocytosis of erythroid elements by histiocytes; vacuolization of erythroid precursors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…These were the nucleoside analogs TF and RV (Knight et al, 1987;Srivastava et al, 1977;Weber et al, 1988;Witkowski et al, 1972). RV has been used clinically as an antiviral, and an increase in platelet numbers has been reported in primate and human subjects given this compound (Cosgriff et al, 1984;Shulman, 1984). Consequently we focused our attention on the effects of this agent, alone, and in combination with cytokines as described below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were the nucleoside analogs TF and RV (Knight et al, 1987;Srivastava et al, 1977;Weber et al, 1988;Witkowski et al, 1972). RV has been used clinically as an antiviral, and an increase in platelet numbers has been reported in primate and human subjects given this compound (Cosgriff et al, 1984;Shulman, 1984). Consequently we focused our attention on the effects of this agent, alone, and in combination with cytokines as described below.…”
Section: Resultsmentioning
confidence: 99%
“…They have been shown to act as differentiation agents in such well known cell lines as K562 and HL-60 (Goldstein et al, 1991;Kharbanda et al, 1988;Yu et al, 1989), as well as in primary cell culture (Wright et al, 1992) and it has been suggested that they function by interfering with the activity of G protein linked signal- ling systems (Wright, 1987). RV has also received application in the clinic as an antiviral agent (Witkowski et al, 1972) and has been reported to increase megakaryocyte and platelet levels in primates including humans (Cosgriff et al, 1984;Shulman, 1984). Consistent with the literature we have found that CMK cells treated with RV showed reduced GTP levels relative t o control cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it has been proposed that anemia during treatment with RBV/IFN is a "mixed" form of anemia, with extravascular hemolysis plus concomitant bone marrow suppression. Although data from animal studies showed some suppressive effect of RBV on erythrocyte production, this has never been confirmed in humans under therapeutic doses [46,47]. However, even during monotherapy with IFN for the treatment of HCV infection mild anemia was observed, and this was not accompanied by compensatory reticulocytosis [14,15,39].…”
Section: Risk Factors For Ribavirin-induced Anemiamentioning
confidence: 99%
“…The CMK cell system described here should permit analysis of the activity of a natural factor, IL-3, on the aspects of early and midphase megakaryocytic development which appear to be recapitulated by this system. While RV is not a physiological factor it should be noted that it does stimulate megakaryocyte and platelet levels in primates and humans when administered clinically (Cosgriff et al, 1984;Shulman, 1984). Its activity displayed in this system may be reflective of its activity in vivo.…”
Section: Discussionmentioning
confidence: 99%